2018
DOI: 10.3389/fpsyg.2018.02196
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perspectives in Episodic Memory and the Sense of Self

Abstract: The connection between memory and self-consciousness has been a central topic in philosophy of memory. When remembering an event we experienced in the past, not only do we experience being the subject of the conscious episode, but we also experience being the protagonist in the memory scene. This is the “phenomenal presence of self.” To explore this special sense of self in memory, this paper focuses on the issue of how one identifies oneself in episodic simulation at the retrieval of memory and draws attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
(82 reference statements)
0
13
0
1
Order By: Relevance
“…According to his view, the observer perspective is an unoccupied point of view-that is, the scene is merely presented from a certain point of view without the experiencer having had the experience of seeing as a character (see also the discussion in §5). The third possibility is supported by Lin (2018Lin ( , 2020, for it enables the best explanation for the subjects' use of first-person pronouns in their reports and data of observer-perspective imagery in sports psychology. The last one has not been considered in the literature; however, since it has been suggested that there may be two visual perspectives involved in the same episode of mental simulation, shifting between the field and observer perspectives is a reasonable possibility to consider.…”
Section: Visual Perspectives and The Sense Of Self In Episodic Simulation: Variety And Limitsmentioning
confidence: 96%
See 2 more Smart Citations
“…According to his view, the observer perspective is an unoccupied point of view-that is, the scene is merely presented from a certain point of view without the experiencer having had the experience of seeing as a character (see also the discussion in §5). The third possibility is supported by Lin (2018Lin ( , 2020, for it enables the best explanation for the subjects' use of first-person pronouns in their reports and data of observer-perspective imagery in sports psychology. The last one has not been considered in the literature; however, since it has been suggested that there may be two visual perspectives involved in the same episode of mental simulation, shifting between the field and observer perspectives is a reasonable possibility to consider.…”
Section: Visual Perspectives and The Sense Of Self In Episodic Simulation: Variety And Limitsmentioning
confidence: 96%
“…rise to the experience of being the same person as the protagonist in imagination, memory or future thinking? The issue of identification has been explored via the capacity to imagine being other people (Dilip 2016;Williams 1973;Wollheim 1973), immunity to error through misidentification (Bermudez 2013;Fernández 2014Fernández , 2018Hamilton 2009; Michaelian 2020), as well as identification in episodic simulation with an observer perspective (Lin 2018(Lin , 2020McCarroll 2018). In regard to the last stream of discussion, in contrast to episodic simulation from a field perspective, in which the perspectival property-the origin of the visual perspective-coincides with the embodied property-the location of one's simulated bodythese two phenomenal properties of bodily self-consciousness are dissociated in OPES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounts of kinds of memory based on empirical research on memory systems, for example, appear to challenge traditional philosophical taxonomies (Andonovski, 2018;Cheng & Werning 2016;Colaço forthcoming;Gomez-Lavin, 2021;Klein, 2015;Michaelian, 2011bMichaelian, , 2015Najenson forthcoming;Werning & Cheng, 2017). Empirically-inspired approaches on which observer memory, in which one adopts a perspective other than that from which one originally experienced the remembered event, can be fully successful similarly appear to challenge traditional philosophical accounts, which may rule out the possibility of successful observer memory (Lin, 2018(Lin, , 2020McCarroll & Sutton, 2017;McCarroll, 2017McCarroll, , 2018Sutton, 2010). And empirically-inspired accounts of collective (Arango-Muñoz, & Michaelian 2020; Barash, 2017;De Brigard, 2018;Michaelian & Sutton, 2017bSeemann, 2019;Sutton, 2018;Theiner, 2013Theiner, , 2017Tollefsen, Dale, & Paxton, 2013;Wilson, 2018) and external (Clowes 2013(Clowes , 2017Heersmink, 2020ab;Heersmink & Carter, 2020;Heersmink & Sutton, 2020;Michaelian, 2012;Rupert, 2013) memory may likewise challenge traditional accounts, which tend to be individualist and internalist in character.…”
Section: Philosophy Of Memorymentioning
confidence: 99%
“…Episodic memory is memory of past events that are "relived". An episodic memory is one that is reconstructed with its spatial, temporal, and self-referential, or phenomenological, context (Gardiner, 2001;Klein, 2015;Lin, 2018;Tulving, 1985).…”
Section: The Existence Of Episodic Memorymentioning
confidence: 99%